The Influence of Fundamental Factors on Stock Returns of Consumer Goods Second Liner Companies on the Indonesia Stock Exchange - Putra, Bebinsa; Setyadi, Bakti (SEIKO : Journal of Management & Business, 2023)
This research aims to analyze the influence of fundamental factors such as Return on Equity, Earning per Share (EPS), Debt to Equity Ratio (DER), Net Profit Margin (NPM), Price to Book Value (PBV), Price to Earnings Ratio (PER) , and Dividend Yield, on stock returns of consumer goods second liner companies on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The method used is panel data with testing using a partial regression test (t test) via the EViews application. The research sample was selected using a purposive sampling technique, involving 25 second liner consumer goods companies that met certain criteria, such as 5-year audited reports, actively traded, and not suspended. The analysis results show that ROE and DER do not have a significant influence on second liner stock returns. Meanwhile, NPM and EPS have a positive and significant influence on second liner stock returns. Meanwhile PBV, PER do not have a significant influence on second liner stock returns and Dividend Yield has a negative and significant influence on second liner stock returns. The implication of these findings is to provide important insights for investors and management of second liner consumer goods companies on the IDX. Company management can focus on increasing NPM and EPS as an effort to increase stock returns. For investors, understanding the fundamental factors that influence stock returns can help in making better investment decisions.